"MUSIC AS A MAIN TOOL IN THE DEVELOPMENT OF SPEAKING SKILLS" - Xakimova Zulfiya Oybek qizi; Sultonova Nigora Abduganievna (TADQIQOTLAR, 2025)
Annotation: Music has proven to be an invaluable tool in enhancing various aspects of language learning, particularly in the development of speaking skills. This article explores the significance of incorporating music into language lessons as a central strategy for improving pronunciation, fluency, and overall speaking confidence. By using music-based activities such as singing, rhythmic exercises, and role-playing, language learners can practice and internalize the natural rhythm and intonation of the language. These activities not only help in mastering pronunciation but also encourage fluidity in conversation and increase learners’ self-assurance when speaking.Through cognitive and emotional engagement, music fosters a deeper connection to the language, aiding in memory retention and vocabulary acquisition. Additionally, music- based tasks can improve both receptive (listening and comprehension) and productive (speaking) language skills, making language learning a more dynamic and enjoyable process. This article emphasizes the effectiveness of music in language teaching and offers practical strategies for teachers to integrate musical elements into their curriculum to create a motivating, effective, and engaging learning environment.